2007
DOI: 10.1109/ivs.2007.4290108
|View full text |Cite
|
Sign up to set email alerts
|

Road Segmentation Supervised by an Extended V-Disparity Algorithm for Autonomous Navigation

Abstract: This paper presents an original approach of road segmentation supervised by stereovision. It deals with free space estimation by stereovision and road detection by color segmentation. The v-disparity algorithm is extended to provide a reliable and precise road profile on all types of roads. The free space is estimated by classifying the pixels of the disparity map. This classification is performed by using the road profile and the u-disparity image. Then a color segmentation is performed on the free space. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 12 publications
0
56
0
Order By: Relevance
“…As a first step, we propose to use a quite opposite scheme, which only assumes that the road is flat. The distance of a pixel in the image is thus assumed given by (4). Large distances are clipped using a parameter c. The distance d c of a pixel P(i, j) is thus expressed by: where N × M denotes the size of the image.…”
Section: Flat World Restorationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a first step, we propose to use a quite opposite scheme, which only assumes that the road is flat. The distance of a pixel in the image is thus assumed given by (4). Large distances are clipped using a parameter c. The distance d c of a pixel P(i, j) is thus expressed by: where N × M denotes the size of the image.…”
Section: Flat World Restorationmentioning
confidence: 99%
“…area is either detected based on color [1] or texture [2] segmentations, deduced from stereovision based obstacles detection [3] or is a combination of both approaches [4]. However, all these methods have difficulties in foggy weather.…”
mentioning
confidence: 99%
“…The v-disparity method [2], [9], [10] is generally used for road surface identification, owing to its simplicity and effectiveness. However, we previously reported that this method became inaccurate when the vehicle was moving fast on a curve.…”
Section: Road Surface Extractionmentioning
confidence: 99%
“…Others include Dahlkamp et al [19], who used self-supervised learning on color images to extend roads found by LADAR. In the area of stereo-vision Soquet et al [20] used a stereo-based color segmentation algorithm to determine road segments. Texture has also been used as seen in Zhang and Nagel [21], who explore anisotropic texture features of roads for segmentation.…”
Section: Path Findingmentioning
confidence: 99%